2020
DOI: 10.1186/s12864-020-6665-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of antibiotics on the gut microbiome: a metagenomics analysis of microbial shift and gut antibiotic resistance in antibiotic treated mice

Abstract: Background: Emergence of antibiotic resistance is a global public health concern. The relationships between antibiotic use, the gut community composition, normal physiology and metabolism, and individual and public health are still being defined. Shifts in composition of bacteria, antibiotic resistance genes (ARGs) and mobile genetic elements (MGEs) after antibiotic treatment are not well-understood. Methods: This project used next-generation sequencing, custom-built metagenomics pipeline and differential abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 65 publications
3
34
1
Order By: Relevance
“…For other pathogens studied, for example Campylobacter coli in the Ciprofloxacin cohort, we found that while the relative abundance is not increased, the numbers of ARGs are, suggesting more ARG-enriched subpopulations were selected by the treatment. Interestingly, our previous study suggested that ARGs enriched in cohorts treated by one class of antibiotics are often resistant to other classes of antibiotics [14]. We also observed that some opportunistic pathogens have more ARG-associated reads in control compared to antibody-treated groups (Fig.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…For other pathogens studied, for example Campylobacter coli in the Ciprofloxacin cohort, we found that while the relative abundance is not increased, the numbers of ARGs are, suggesting more ARG-enriched subpopulations were selected by the treatment. Interestingly, our previous study suggested that ARGs enriched in cohorts treated by one class of antibiotics are often resistant to other classes of antibiotics [14]. We also observed that some opportunistic pathogens have more ARG-associated reads in control compared to antibody-treated groups (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…All mice, except two of the three control mice, were inoculated with CFT073 uropathogenic E.coli (ATCC, Manassas, VA) to create the UTI model. Our previous study showed no discernable difference in the gut microbiome of naïve and urinary tract infection model mice [14]. Treatment groups include antibiotics Ampicillin, Ciprofloxacin, and Fosfomycin.…”
Section: Animal Studiesmentioning
confidence: 90%
See 2 more Smart Citations
“…Interestingly, acrB, an efflux membrane transporter that conferred resistance to several antibiotics classes, negatively associated with diet and was not among the top-ten ARGs of juveniles. Efflux pumps are a part of bacteria’s intrinsic resistance mechanism and decrease different antibiotic concentrations within the cell wall [ 55 ]. Since efflux pumps can be transferred horizontally [ 56 ], the presence of acrB in adults and geriatrics could be involved in horizontal gene transfer events [ 57 ].…”
Section: Discussionmentioning
confidence: 99%